2014
DOI: 10.1021/cg500136v
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Reversible Crystal Transformation of Cu(I) Supramolecular Isomers

Abstract: Four copper(I) coordination polymers (CPs), {[CuIL]·CH3CN]} n (1), {[CuIL]·CHCl3} n (2), {[CuIL]·CH2Cl2} n (3), and [CuIL] n (4), were prepared by self-assembly reactions between CuI and (2-pyrazinylcarbonyl)thiomorpholine (L). CPs 1–4 are interconnected by rhomboid Cu–I2–Cu units. CPs 1 and 4 have one-dimensional loop-chain structures, and 2 and 3 adopt two-dimensional network structures. CPs 1–4 are pseudopolymorphic supramolecular isomers. CPs 2′ and 3′ are prepared by removal of solvate molecules from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Examples exist whereby reversible single crystal single crystal transformations mediated by solvent guests [90,91], recrystallization [92] and microwave irradiation/rehydration [93,94]. (7) it was concluded that adventitious water mediated the in situ transformation of 6 to 7 [50].…”
Section: Conversion Between Simentioning
confidence: 99%
“…Examples exist whereby reversible single crystal single crystal transformations mediated by solvent guests [90,91], recrystallization [92] and microwave irradiation/rehydration [93,94]. (7) it was concluded that adventitious water mediated the in situ transformation of 6 to 7 [50].…”
Section: Conversion Between Simentioning
confidence: 99%
“…[10][11][12] Luminescence thermochromism 13 and mechanochromism 14 of copper(I) complexes have been studied. Recently, we have concentrated on our research about Cu(I) coordination polymers based on dithioether ligands [15][16][17] and reported on luminescence thermochromism, 15 preparation of γ-CuI nanoparticle, 18 crystal-to-crystal transformation, 19 and so on. During our investigation on the copper(I) complexes of dithioether ligands, no photoluminescence was observed from rhomboid Cu 2 I 2 complexes.…”
mentioning
confidence: 99%
“…Acetonitrile played a key role in solvent exchange by opening the space inside the CP framework, and although reversible transformation was seen, crystal transformation based on solvent vapor was not observed. 16 We therefore chose to investigate the possibility of reversible crystal transformations induced by volatile organic compound (VOC) vapors by employing ligand conformation change and crystal-to-amorphous-to-crystal (CAC) transformations, according to stepwise stimulation by heat and solvent vapors. 18−21 A dithioether ligand, N,N′-bis [2-(cyclohexylthio)ethyl] pyromellitic diimide (L), bearing an electron-deficient pyromellitic diimide spacer was synthesized by reacting pyromellitic dianhydride with 2-(cyclohexylthio)ethylamine according to a previous literature method.…”
mentioning
confidence: 99%
“…As shown in Figure 2b, CPs 1−3 showed reversible solvent exchange according to the specific ratios of VOC vapors, and as a result, transformation between the crystals occurred more readily. 16,23 We investigated whether powdered specimens of CPs 1−3 exhibited vapochromism when coated on a glass slide (left to right) and exposed to a mixed solvent vapor with a specific ratio at room temperature ( Figure S9 in the SI). 24,25 When the prepared specimens were exposed to the vapor of a dichloromethane/acetonitrile 5:1 mixture, CPs 2 and 3 exhibited comparable luminescence with CP 1, thus being in accord with solvent exchange using dichloromethane and structural transformation from CPs 2 and 3 to CP 1.…”
mentioning
confidence: 99%